Release of cations from vermi culite mixed with soils - Marconi, Arary; Abrahão, Ibrahim Octavio; Kinjo, Toshiaki; Silveira, Ronaldo Ivan (Anais da Escola Superior de Agricultura Luiz de Queiroz, 1987)
The release of cations from the vermiculite in soils as a consequence of weathering processes was studies. Vermiculites, in two different particle-sizes, were mixed with sandy and clayey soils of low fertility, at the rate of 20% vermiculite, and treated with water acidified to pH 5. The results of chemical analyses showed that a large amount of soluble cations, such as calcium, magnesium, and potassium, was removed from the vermiculite, white silicon, aluminum, and iron tended to remain in the system. As a secondary effect, an increase in soil pH, as a consequence of the release of cations, was observed.